Amino Acid Hydration Decreases Radiation-Induced Nausea in Mice: A Pica Model - Yin, Liangjie; Vaught, Lauren; Okunieff, Paul; Casey-Sawicki, Katherine; Vidyasagar, Sadasivan (Advances in experimental medicine and biology, 2017)
Nausea and diarrhea are common yet inconsistent side effects of abdominal and pelvic irradiation. Their frequency, chronicity, and severity vary greatly, and the reasons for inter-subject variability are unknown. We studied the potential for radiation-induced changes in amino acid absorption and mucosal barrier function to lead to gastrointestinal toxicity. We found profound and prolonged changes in the absorption and secretion of several electrolytes and nutrients, caused by changes in transporter function, after radiation doses as low as 1 to 3 Gy. After identifying absorbed and non-absorbed amino acids, we demonstrated the role of a beneficial amino acid drink to alleviate radiation-related gastrointestinal symptoms in a mouse model.